2021
DOI: 10.3390/antibiotics10050509
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Interventions to Prevent and Control Carbapenem-Resistant Enterobacteriaceae and Extended-Spectrum β-Lactamase Producer-Associated Infections at a Tertiary Care Hospital in Egypt

Abstract: The current rise of multidrug-resistant (MDR) Gram-negative Enterobacteriaceae including the extended-spectrum β-lactamase (ESBL)-producing organisms and carbapenem-resistant Enterobacteriaceae (CRE) has been increasingly reported worldwide, posing new challenges to health care facilities. Accordingly, we evaluated the impact of multimodal infection control interventions at one of the major tertiary healthcare settings in Egypt for the aim of combating infections by the respective pathogens. During the 6-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
0
7
1
Order By: Relevance
“…In terms of its accuracy in detecting antimicrobial resistance genes, BFPP showed relatively high agreement when compared to VITEK-2 breakpoints, with PPA [100%, 93%, not applicable], NPA [97%, 85%, 90%], and OPA [98%, 90%, 90%] for carbapenemase producers, ESBLs, and MRSA, respectively. In comparison to other studies [28,[39][40][41] that reported on the prevalence of carbapenemase producers and ESBLs among HAP patients, our results revealed a higher rate of detection. This higher resistance rate could be attributed to the large use of antimicrobial agents among ICU patients, leading to more selective pressure and the appearance of different resistant phenotypes.…”
Section: Discussioncontrasting
confidence: 91%
“…In terms of its accuracy in detecting antimicrobial resistance genes, BFPP showed relatively high agreement when compared to VITEK-2 breakpoints, with PPA [100%, 93%, not applicable], NPA [97%, 85%, 90%], and OPA [98%, 90%, 90%] for carbapenemase producers, ESBLs, and MRSA, respectively. In comparison to other studies [28,[39][40][41] that reported on the prevalence of carbapenemase producers and ESBLs among HAP patients, our results revealed a higher rate of detection. This higher resistance rate could be attributed to the large use of antimicrobial agents among ICU patients, leading to more selective pressure and the appearance of different resistant phenotypes.…”
Section: Discussioncontrasting
confidence: 91%
“…Overnight cultures of tested isolates were grown in Luria Bertani (LB) broth containing 25 µg/mL meropenem. PCR detection and conditions of carbapenemaseencoding genes was carried out using PCR as previously described [25]. The set of 5 primers with the corresponding annealing temperatures and expected amplicon sizes was shown in supplementary file (Table S1).…”
Section: Molecular Characterization Of Carbapenemase Producing Gnbmentioning
confidence: 99%
“…Comparing the efficacy of colistin with other agents for the treatment of CR-GNB infections is extremely difficult due to the large number of different treatment regimens in the comparator arms, the frequent use of combination regimens in both the colistin arm and the comparator arms, and the suboptimal dosing of colistin in many studies. Numerous studies have revealed that almost half of patients treated with colistin for CR-GNB infections develop AKI, and up to two-thirds of these patients have 30-day or in-hospital mortality [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Similarly, poor clinical outcomes (e.g., high clinical failure and prolonged hospital stay) were documented with colistin-based regimens for treating CR-GNB infections [ 77 , 78 , 79 , 80 ].…”
Section: Colistin Vs Novel Blblis For the Treatment Of Cr-gnb Infectionsmentioning
confidence: 99%